2017
DOI: 10.1002/mus.25981
|View full text |Cite
|
Sign up to set email alerts
|

Charcot–Marie–Tooth Disease type 4C: Novel mutations, clinical presentations, and diagnostic challenges

Abstract: A new era of unbiased genetic testing has led to this small case series of individuals with CMT4C and highlights the recognition of different genetic diseases in CMT4C patients for accurate diagnosis, genetic risk identification, and therapeutic intervention. The phenotype of CMT4C, in addition, appears to be enriched by a number of features unusual for the broad CMT category. Muscle Nerve 57: 749-755, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…2 9 The SH3TC2 gene encodes a protein with two SH3 domains and ten tetratricopeptide repeats 2 (TC2) motifs, involved in the myelin layer formation by the Schwann cells. 10 SH3TC2 mutations disrupt the interaction with GTPase (guanosine triphosphatase) Rab11, a key regulator in recycling the endosome functions, resulting in impaired myelination by Schwann cells as this SH3TC2/Rab11 interaction is required for normal myelination. 11 CMT4C has an autosomal recessive mode of Mendelian inheritance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 9 The SH3TC2 gene encodes a protein with two SH3 domains and ten tetratricopeptide repeats 2 (TC2) motifs, involved in the myelin layer formation by the Schwann cells. 10 SH3TC2 mutations disrupt the interaction with GTPase (guanosine triphosphatase) Rab11, a key regulator in recycling the endosome functions, resulting in impaired myelination by Schwann cells as this SH3TC2/Rab11 interaction is required for normal myelination. 11 CMT4C has an autosomal recessive mode of Mendelian inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…12 The phenotypic variability and associations of CMT4C may be due to the cryptogenic modifiers or the SH3TC2 protein diversity. 10 In 2015, Kalane et al 13 reported the first case of CMT4C in a 10-year-old Indian girl with a homozygous nonsense variation c. 2710C > T in exon 11 of the SH3TC2 gene, with bilateral mild pes cavus foot deformities without any spinal deformity. In 2018, Jerath et al 10 reported associations of CMT4C with other rare diseases such as Von-Willebrand disease type 2M, short-chain acyl-coenzyme A dehydrogenase deficiency, retinitis pigmentosa, and plasminogen activator inhibitor-1 deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenotype of patient S.11 with homozygous SH3TC2 variants and CMT4C has been reported. 13 An adult female (S.15) with a PNPLA6 variant had juvenile-onset MND with distal weakness most marked in finger flexion, ankle dorsiflexion and toe extension.…”
Section: Clinical Presentations In Patients With Novel Pathogenic Variantsmentioning
confidence: 99%